Blurred Lines in Allegations of Musical Intertextuality: A Response to Orosz - de Clercq, Trevor; Wagnon, Deborah (Empirical Musicology Review, 2023)
This commentary responds to Orosz’s recent EMR article, which presents research on the accuracy of user-generated information on the whosampled.com website. In general, we find Orosz’s main conclusions—that the accuracy of an entry tends to relate to the type of sample (direct or interpolated), how distinct the sample is, and the style of music—are convincing and well-supported by examples. That said, we believe Orosz’s ultimate appraisal of the web site as an invaluable resource to be contingent on the user. From the viewpoint of a music theorist such as Orosz, the web site may indeed be a beneficial resource. But for other users, especially students aspiring to create popular music, a lack of education about the legal issues surrounding the web site may foster a problematic perspective on music sampling.